Challenges Dealing with Community Demands: Portrait of Corporate Social Responsibility in A Fishery Company - Koan, Dianne Frisko; Hartanto, Melina Cahyo (Devotion: Journal of Community Service, 2022)
Corporate Social Responsibility (CSR) was considered an output from the business sectors to show their commitment in responding to stakeholder interests beyond profit. This study aims to explore more on the practice of CSR and how a company manage its stakeholder interest. Therefore, this qualitative study uses a case study method to get the actual description from the primer sources. This case study collects data from a fishery company located in East Java, Indonesia. Various instruments of data collection are used in this study, including in-depth interviews and group discussions with the company and its stakeholder, also observations on some relevant events to enrich the data. The total of respondents who participated in this case study is seven persons. In addition, the document analysis collected from the external and internal companies has been done to strengthen the data analysis and conduct the triangulation within various collected data. This study found that a company needs to maintain their relationship with the community while undertaking its CSR programs. Stakeholder engagement activity must be considered start before a company designs its CSR program and periodically monitors and evaluates the CSR program.